2007
DOI: 10.1177/0022487107305259
|View full text |Cite
|
Sign up to set email alerts
|

What Teacher Candidates Learned About Diversity, Social Justice, and Themselves From Service-Learning Experiences

Abstract: This article examines how service-learning provides undergraduate teacher candidates opportunities to cultivate deeper understandings of diversity, social justice, and themselves. Participants were from a mid-Atlantic university and a rural southeastern university. Although from different regions, the teacher candidates shared predominantly White, middle-class backgrounds. Three themes framed the discussion—preconceived notions about teaching in diverse settings, how preconceived notions were overcome (or rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
22

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(168 citation statements)
references
References 17 publications
(22 reference statements)
4
127
0
22
Order By: Relevance
“…Their learning has a transformative potential that is, as yet, not possible within and through the traditional approaches to pre-service education programs. As Baldwin, Buchanan and Rudisill (2007) argue, "Service-learning has the potential for development TCs'[teacher candidates'] abilities to question their own assumptions, societal inequities, and existing curriculum" (p. 318).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their learning has a transformative potential that is, as yet, not possible within and through the traditional approaches to pre-service education programs. As Baldwin, Buchanan and Rudisill (2007) argue, "Service-learning has the potential for development TCs'[teacher candidates'] abilities to question their own assumptions, societal inequities, and existing curriculum" (p. 318).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the two researchers were assisted by a research assistant to verify data interpretation for link with theory and practice. The data was also compared with findings from other literature on Service-learning (Baldwin, Buchanan & Rudisill, 2007) so that criteria could be developed to establish the validity of the data that was collected and analysed.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The suggestion of Agarwal et al presupposes emancipatory pedagogical endeavours. According to Baldwin, Buchanan and Rudisill (2007) this adds a dimension of social justice that requires teachers to critically analyse the perceived realities of social and environmental injustices that affect teaching, learning, and the curriculum. Teachers need therefore, to understand their broader role as agents of change and development; as agents in addressing rural education as a human right and a social justice issue.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature (Baldwin, Buchanan, and Rudisill 2007;Banks and Banks 1995;Tomalin 2007) in the field paints an unfavourable picture arguing that in many cases there is a perception that ethnically diverse students have low capability, poor skills, lack intelligence, are difficult to work with, and apt to cause discipline problems (Baldwin, Buchanan, and Rudisill 2007). In addition to these perceptions, Habu (2000) found that ethnically diverse students complain they are not taken seriously and are viewed as a source of income as opposed to learners.…”
Section: Theme 3: Student Capability and Skillsmentioning
confidence: 99%